2021
DOI: 10.4018/ijide.2021040102
|View full text |Cite
|
Sign up to set email alerts
|

Creating Inclusive Workplaces for Women in Health Organizations Engaging in Digital Economy-Driven Innovations

Abstract: The digital economy is creating significant innovations in healthcare. Thriving in this new digital era requires all kinds of healthcare organizations to shift their cultural and organizational mindsets to be more adaptive. The new adaptability means letting go of outdated business cultures and processes, especially those that not inclusive and respectful of women and their professional contributions. This case study reflects an IT healthcare organization in which several senior managers inappropriately harass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Psychologically, (Barrientos et al, 2019;Belwal & Belwal, 2017) states that if women work, then women undergo very heavy multiple roles and responsibilities that allow the emergence of superwoman syndrome. Therefore, the results showed that female workers who are not bound by marriage have the highest productivity compared to married female workers, especially those who already have children, even though their husbands also work (Autin et al, 2022;Burrell et al, 2021).…”
Section: Work Productivity Of Women Workersmentioning
confidence: 96%
“…Psychologically, (Barrientos et al, 2019;Belwal & Belwal, 2017) states that if women work, then women undergo very heavy multiple roles and responsibilities that allow the emergence of superwoman syndrome. Therefore, the results showed that female workers who are not bound by marriage have the highest productivity compared to married female workers, especially those who already have children, even though their husbands also work (Autin et al, 2022;Burrell et al, 2021).…”
Section: Work Productivity Of Women Workersmentioning
confidence: 96%